2022
DOI: 10.1002/btm2.10448
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord tissue engineering using human primary neural progenitor cells and astrocytes

Abstract: Neural progenitor cell (NPC) transplantation is a promising approach for repairing spinal cord injury (SCI). However, cell survival, maturation and integration after transplantation are still major challenges. Here, we produced a novel centimeter‐scale human spinal cord neural tissue (hscNT) construct with human spinal cord neural progenitor cells (hscNPCs) and human spinal cord astrocytes (hscAS) on a linearly ordered collagen scaffold (LOCS). The hscAS promoted hscNPC adhesion, survival and neurite outgrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Aligned structural scaffolds have been extensively studied for spinal nerve regeneration, since they are known to facilitate the directed growth of axons. , Aligned fibrin or aligned fibrin/functionalized self-assembling peptide interpenetrating nanofiber hydrogel enhanced axonal regeneration compared to hollow conduits, and aligned collagen/fibrin hydrogel nanofibers loaded with SDF1α promoted the directed migration and differentiation of endogenous stem cells . Our previous studies demonstrated axons extending directionally on linearly ordered collagen scaffold (LOCS) like axons in centimeter-scale human spinal cord neural tissue constructed by human spinal cord neural progenitor cells and human spinal cord astrocyte were arranged in LOCS orderly . In this study, a series of physical, chemical, and enzymatic treatments were used to remove cellular components from porcine spinal cord tissues.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aligned structural scaffolds have been extensively studied for spinal nerve regeneration, since they are known to facilitate the directed growth of axons. , Aligned fibrin or aligned fibrin/functionalized self-assembling peptide interpenetrating nanofiber hydrogel enhanced axonal regeneration compared to hollow conduits, and aligned collagen/fibrin hydrogel nanofibers loaded with SDF1α promoted the directed migration and differentiation of endogenous stem cells . Our previous studies demonstrated axons extending directionally on linearly ordered collagen scaffold (LOCS) like axons in centimeter-scale human spinal cord neural tissue constructed by human spinal cord neural progenitor cells and human spinal cord astrocyte were arranged in LOCS orderly . In this study, a series of physical, chemical, and enzymatic treatments were used to remove cellular components from porcine spinal cord tissues.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Female SD rats weighing 220−250 g were completely traversed about 3 mm at the thoracic 8−10 segment according to our previous study. 49 They were randomly divided into five groups (10 rats/ group): SCI, A-CF, A-DSCF, A-CF/NPC (loaded with a total of 1 × 10 6 GFP + cells per scaffold), and A-DSCF/NPC (loaded with a total of 1 × 10 6 GFP + cells per scaffold). After the surgery, the rats were given penicillin streptomycin and glucose for 1 week, and their bladders were manually squeezed twice a day to facilitate urine elimination until the restoration of urinary reflex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have fabricated novel centimetre-scale human spinal cord neural tissue constructs with human spinal cord NPCs and astrocytes combined with a linearly ordered collagen scaffold. In this case, astrocytes could facilitate NPC adhesion and neurite outgrowth on the collagen scaffold, forming a linearly ordered spinal cord-like structure comprising mature neurons and glia cells [ 212 ].…”
Section: Therapeutic Applications Of Collagen-based Biomaterials In N...mentioning
confidence: 99%